Faktor - Faktor yang Berhubungan dengan Keaktifan Ibu dalam Mengikuti Kelas Ibu Hamil di Wilayah Kerja Puskesmas Babat Toman Kabupaten Musi Banyuasin - Felina, Firna; Mastina, Mastina; Effendi, Hazairin (Universitas Malahayati, 2024)
ABSTRACT The most important thing is that the implementation of classes for pregnant women must be accompanied by knowledge and attitude, because without the knowledge and attitude that pregnant women have, they cannot carry out exercise techniques well and feel the benefits. (Lumbantobing & Nababan, 2021). The aim of this research is to determine knowledge, employment status and family support with the activeness of pregnant women in attending classes for pregnant women in the working area of the Babat Toman Community Health Center, Musi Banyuasin Regency in 2023. This research uses an analytical survey method using a